Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1080/10438599.2015.1076203
|View full text |Cite
|
Sign up to set email alerts
|

R&D investments, financing constraints, exporting and productivity

Abstract: This paper adds new empirical evidence on the mutual relationships between credit constraints, total factor productivity, Research and Development (R&D) investments and exporting, by jointly considering them in a simultaneous equation framework. Our empirical analysis focuses on a large sample of manufacturing firms from France, Germany, Italy and Spain. Our results confirm the well-known mutual positive correlation among exporting, R&D and firm's productivity. They also show the existence of a mutual relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 39 publications
2
35
0
Order By: Relevance
“…This may 8 Altomonte et al (2013) use the proportion of firms benefiting from R&D public support at sector-by-country level, as well as the average share of R&D expenses over sales, to predict the innovation capability of the firm, and through this channel, the firm propensity to operate in international markets. Aristei et al (2016) and Altomonte et al (2016) use similar identification strategies. 9 Our set of estimates is not affected by under-identification problems as Kleibergen Paap rk LM test ranges from 83.6 to 221.9. be due to the fact that the use of external instruments helps eliminating the effect of some omitted factors that are correlated with both the labour share and internationalisation variables, hence producing a downward bias in the OLS coefficient.…”
Section: Endogeneity Issuesmentioning
confidence: 99%
“…This may 8 Altomonte et al (2013) use the proportion of firms benefiting from R&D public support at sector-by-country level, as well as the average share of R&D expenses over sales, to predict the innovation capability of the firm, and through this channel, the firm propensity to operate in international markets. Aristei et al (2016) and Altomonte et al (2016) use similar identification strategies. 9 Our set of estimates is not affected by under-identification problems as Kleibergen Paap rk LM test ranges from 83.6 to 221.9. be due to the fact that the use of external instruments helps eliminating the effect of some omitted factors that are correlated with both the labour share and internationalisation variables, hence producing a downward bias in the OLS coefficient.…”
Section: Endogeneity Issuesmentioning
confidence: 99%
“…James Brown and Bruce Petersen (2009) studied US firms' investment-cash flow sensitivity and found a strong negative relationship between cash flow and R&D investment, interpreting this as sign of financing constraints. Similar results were found for France (Philippe Aghion et al 2008), Germany (Hottenrott and Bettina Peters 2012), Portugal (Filipe Silva and Carlos Carreira 2012), S. Korea (Sanghoon Lee 2012) and transition economies (Yuriy Gorodnichenko and Monika Schnitzer 2013;Kadri Männasoo and Jaanika Meriküll 2014). In a recent study, Neil Lee, Hiba Sameen, and Marc Cowling (2015) found that there is a structural problem in the financial system that constrains finance for innovative firms with a sample of small-and medium-sized UK firms.…”
Section: Financing Constraints and Randd Investmentmentioning
confidence: 53%
“…Firstly, this study complements and builds on the findings of previous studies that have particular interests on understanding: (1) Which financial factors influence RDI performance of high‐tech companies (e.g., Minola and Giorgino, ; Altomonte et al, ); (2) How RDI investment financing takes place in the emerging market context (e.g., Zhang et al, ; Alam et al, ); (3) How effective financial support in stimulating RDI is (e.g., Kaufmann and Tödtling, ; Yigitcanlar et al, ).…”
Section: Discussionmentioning
confidence: 67%